2005
DOI: 10.1111/j.1365-2958.2005.04727.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest during S or M phase generates polarized growth via distinct signals in Candida albicans

Abstract: SummaryTreatments that perturb DNA synthesis or mitosis will activate checkpoints that prevent cell cycle progression and cell proliferation. In yeast-form cells of the fungal pathogen Candida albicans , exposure to hydroxyurea (HU) or shutting off expression of the polo-like kinase CaCDC5 blocked nuclear division and spindle elongation, but activated a highly polarized growth mode. We have used transcription profiling both to characterize the initiation and progression of this polar growth pattern and to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 66 publications
9
129
0
Order By: Relevance
“…The filaments resemble serum-induced hyphae, and filament formation is independent of Cph1 or Efg1 but requires Cyr1/Cdc35 (11). Microarray experiments confirmed the resemblance of cell cycle-arrested filaments to serum-induced hyphae, as in both cases several targets of hyphasignaling pathways were expressed (10).…”
Section: Other Positive Regulators: Cdc5 G 1 Cyclins Int1 Mcm1 Ansupporting
confidence: 48%
“…The filaments resemble serum-induced hyphae, and filament formation is independent of Cph1 or Efg1 but requires Cyr1/Cdc35 (11). Microarray experiments confirmed the resemblance of cell cycle-arrested filaments to serum-induced hyphae, as in both cases several targets of hyphasignaling pathways were expressed (10).…”
Section: Other Positive Regulators: Cdc5 G 1 Cyclins Int1 Mcm1 Ansupporting
confidence: 48%
“…Previous work demonstrated that lower ergosterol levels, caused by ergosterol biosynthesis inhibitors, such as azoles, have an inhibitory effect on hypha formation (63,64). However, elongated growth forms resulting from impaired Hsp90 function are not considered true hyphae (14,65,66). Consistent with the relationship between ergosterol depletion and C. albicans morphogenesis mentioned by Victoria et al (67), we report a correlation between ergosterol content and elongated growth caused by impairment of Hsp90 function.…”
Section: Discussionsupporting
confidence: 79%
“…Transcriptional profiling of HU-treated and cdc5 mutant strains showed different expression patterns. The HU-arrested cells require Ras1p for the extended bud growth, and the cdc5-arrested cells require Bub2p function for the formation of the extended buds (6). The different triggers stop the cells at different points in the cell cycle, and the hyperpolarized bud does not arise because the cells are trapped at a point corresponding to normal polarized growth.…”
Section: Hyperpolarized Budsmentioning
confidence: 99%